The characterisation of protein-rich food waste and pond sludge for biomethane recovery / Rafidah Selaman and Tanto Pratondo Utomo - Selaman, Rafidah; Utomo, Tanto Pratondo (Universiti Teknologi MARA, Sabah, 2024)
Biomethane is a non-renewable energy source that can be produced through the decomposition of biomass. Biomethane has comparable properties to natural gas and, thus, can be transported and stored in the available facilities and infrastructure. Currently, anaerobic digestion (AD) is one of the most favourable techniques that can be used to recover biomethane, as it is a simple and low-cost technology. Protein-rich food waste (PRFW) is one of the food waste compositions that is produced abundantly, and pond sludge (PS) is made of organic materials that enter the ponds, and sink to the bottom, and decompose. Both are claimed to contain high carbon values. Therefore, this study was carried out to determine the physical and biological properties of both substrates and identify the biomethane recovery value through single and mixed digestion. The AD process was performed at mesophilic conditions 35oC (±1) and a pH range of 6.8 to 7.2 for 30 days. The TS values for PRFW and PS were 34.16% (± 0.08) and 40.23% (± 0.06), respectively. While the VS values for PRFW and PS were 88.56% (± 0.04) and 84.30% (± 0.06), respectively. Both substrates also show the availability of facultative anaerobic bacteria (FAB). Hence, this shows the suitability of both substrates to undergo the AD process. Results for biomethane recovery found that mixing digestion between PRFW and PS recovered the highest amount of biomethane with 120.3 mL (±0.05), and the optimum time for digestion was on day 18. While single digestion of PS and PRFW recovered biomethane with 95.0 mL (±0.12) and 79.3 mL (±0.21) on day 21 respectively. The better synergistic effect within FAB in mixing substrates eventually influences the highest biomethane removal from the substrate in a short period of time. Moreover, this study also provides information on new strategies for recovering biomethane.